Relationship between the equatorial electrojet and global Sq currents at the dip equator region - Hamid, Nurul Shazana Abdul; Liu, Huixin; Uozumi, Teiji; Yumoto, Kiyohumi; Veenadhari, B.; Yoshikawa, Akimasa; Sanchez, Jairo Avendaño (My University, 2014)
The equatorial electrojet (EEJ) is a strong eastward ionospheric current flowing in a narrow band along the dip equator. In this study, we examined the EEJ-Sq relationship by using observations at six stations in the South American, Indian, and Southeast Asian sectors. The analysis was carried out with data on geomagnetically quiet days with Kp ≤3 from 2005 to 2011. A normalization approach was used because it yields more accurate results by overcoming the uncertainties due to latitudinal variation of the EEJ and Sq. A weak positive correlation between the EEJ and Sq was obtained in the Southeast Asian sector, while weak negative correlations were obtained in the South American and Indian sectors. EEJ-Sq relationship is found to be independent of the hemispheric configuration of stations used to calculate their magnetic perturbations, and it also only changed slightly during low and moderate solar activity levels. These results demonstrate that the Southeast Asian sector is indeed different from the Indian and South American sectors, which is indicative of unique physical processes particularly related to the electro-dynamo. Furthermore, we also demonstrate that the definition of the EEJ, that is, the total current or enhanced current, can significantly affect the conclusions drawn from EEJ-Sq correlations.
Keywords: H component; Equatorial electrojet; Sq current; Longitudinal dependence; EEJ